2014
DOI: 10.2527/jas.2013-7056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternate-day feeding of dried distiller's grain plus solubles to forage-fed beef cows in mid- to late gestation1

Abstract: Forty-six nonlactating beef cows were used to examine effects of dried distiller's grains plus solubles (DG) supplementation strategies to cows fed grass hay during mid- to late gestation on BW, ultrasound body composition characteristics, concentrations of serum NEFA and urea, feeding behavior, and calf birth weight. Cows were assigned to dietary treatments in a completely randomized design: 1) control, where hay was fed each day of the week (CON), 2) both hay and DG fed daily during the week (DG7), 3) hay fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Also, BW and BCS change from d 0 to calving did not differ between S3 and S7 cows (P ≥ 0.38; Table 2). Likewise, Klein et al (2014) observed similar BW and BCS change of mid-to late-gestating cows offered free choice access to bromegrass hay and supplemented with dried distillers' grains daily or 3 times weekly (daily supplementation rate = 0.4% of BW, DM basis). Our results agree with others (Drewnoski et al, 2011;Moriel et al, 2012) and also support our previous study that demonstrated that reducing the frequency of WBG supplementation (0.5 or 1.0% of BW, DM basis) from daily to 3 times weekly did not reduce growth of recently weaned beef heifers (Artioli et al, 2016).…”
Section: Precalving Phasementioning
confidence: 59%
See 1 more Smart Citation
“…Also, BW and BCS change from d 0 to calving did not differ between S3 and S7 cows (P ≥ 0.38; Table 2). Likewise, Klein et al (2014) observed similar BW and BCS change of mid-to late-gestating cows offered free choice access to bromegrass hay and supplemented with dried distillers' grains daily or 3 times weekly (daily supplementation rate = 0.4% of BW, DM basis). Our results agree with others (Drewnoski et al, 2011;Moriel et al, 2012) and also support our previous study that demonstrated that reducing the frequency of WBG supplementation (0.5 or 1.0% of BW, DM basis) from daily to 3 times weekly did not reduce growth of recently weaned beef heifers (Artioli et al, 2016).…”
Section: Precalving Phasementioning
confidence: 59%
“…Likewise, Artioli et al (2016) reported similar overall intake of hay DM, total DM, CP, and NEg between recently weaned beef heifers supplemented with WBG (0.5 or 1.0% of BW, DM basis) daily or 3 times weekly. Also, Klein et al (2014) observed similar total and hay DMI of mid-to late-gestating cows offered free choice access to bromegrass hay and supplemented with dried distillers' grains daily or 3 times weekly.…”
Section: Precalving Phasementioning
confidence: 62%
“…It is also accepted that global (energy) nutrition has a greater impact than protein nutrition (Holland and Odde, ; Greenwood and Café, ) which is contrary to the results reported here. However, recent studies (Stalker et al., ; Martin et al., ; Larson et al., ; Bohnert et al., ; Klein et al., ) in which protein supplements were fed to beef cows in mid/late gestation have reported increases in calf birth and/or weaning BW, although in some cases responses were not significant. In these studies, protein intakes were increased by feeding a supplement to cows grazing low‐quality forage and therefore not only protein but also energy intakes would have increased (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, protein intakes were increased by feeding a supplement to cows grazing low‐quality forage and therefore not only protein but also energy intakes would have increased (e.g. by 1.5‐fold; Klein et al., ). Therefore, responses in cow and calf performance could not be solely attributed to increased protein supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation